Synthesis of Mesoporous Silica from Palm Oil Boiler Ash (MS-POBA) with Addition of Methyl Ester Sulfonate as a Template for Free Fatty Acid Adsorption from Crude Palm Oil (CPO) - Sitohang, Cita; Kuncaka, Agus; Suratman, Adhitasari (Universitas Gadjah Mada, 2024)
The synthesis of mesoporous material by utilizing palm oil boiler ash (POBA) waste as the silica source and methyl ester sulfonate (MES) surfactant as the template for a high-porosity was investigated for free fatty acids (FFA) adsorption. The research was initiated with silica extraction from POBA by sodium hydroxide addition through the sol-gel precipitation method. Silica modification was carried out with MES surfactant and 3-aminopropyltrimethoxysilane (APTMS) as the co-structure-directing agent (CSDA) in different calcination temperatures. Mesoporous silica-POBA (MS-POBA) free template had a surface area, pore diameter, and pore volume (41.033 m2/g, 4.180 nm, and 0.250 cm3/g) lower than MS-POBA with the template (71.0147 m2/g, 7.923 nm, and 0.524 cm3/g). The ability of MS-POBA to adsorb FFA reached its optimum conditions with an adsorption time of 20 min and an adsorbent dosage of 0.24 g. The FFA removal by MS-POBA with the template was found to have higher adsorption ability, which was 35.54%, compared to the MS-POBA free template of 26.68%. The high porosity of MS-POBA with a template makes the FFA adsorption capacity of this material higher than MS-POBA free template.